A recipe for success? A nutrient analysis of recipes promoted by supermarkets - Wademan, Jasmin; Myers, G.; Finch, A.; Dhaliwal, Satvinder; Scott, Jane; Begley, Andrea (MDPI, 2020)
Recipe use impacts eating habits, yet there is limited research investigating the nutritional quality of recipes. Supermarket recipe magazines command large readerships, with over 4 million readers for each of the two major Australian supermarket publications. Assessing the nutrient content of featured recipes is therefore of public health interest. The nutrient content of 312 main-meal recipes from Coles® Magazine and Woolworths Fresh® were analyzed and compared against a traffic-light system for classifying nutrients of concern in chronic disease. Nutrient content was compared across recipe type (standard, advertorial and celebrity) and between recipes with and without health or nutrient claims. Overall compliance with the traffic-light criteria was low, with less than half of recipes meeting the target. Advertorial recipes had a higher energy (p = 0.001), saturated fat (p = 0.045) and sodium (p ≤ 0.001) content per serve, and per 100 g for sodium (p ≤ 0.001) compared to standard and celebrity recipes. Recipes with claims had greater compliance to the nutrient criteria (p < 0.001) compared to those without. These findings support previous research highlighting the poor nutritional quality of published recipes from a variety of sources.